THE ARTISTIC INTERPRETATION OF THE THEME OF LOVE IN THE DEPICTION OF THE FEMALE PSYCHE (Intent Research Scientific Journal, 2025)
This article highlights the artistic skill of Guljamol Askarova, a talented representative of modern Uzbek poetry, in illuminating the female psyche through her interpretation of her romantic lyrics.